PERCEPTION OF JUSTICE OVER APPLICATION GOVERNMENT REGULATION NUMBER 58 OF 2023 CONCERNING INCOME TAX ARTICLE 21 : (A CASE STUDY ON PT. KUBU INDAH RESORT) - Suarya, Wayan Bhaskara Sky; Yasa, I Nyoman Putra (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This research was conducted to examine the perspective of taxpayers on the implementation of Government Regulation Number 58 of 2023 on the emergence of overpaid conditions (LB) which should be the reownership of employees at PT. Kubu Indah Resort. The research method used in this study is a qualitative method with a case study approach using the Source Triangulation analysis method. The results of this study state that the perspective of taxpayers (employees) on the implementation of Government Regulation Number 58 of 2023 does raise questions about the right to LB, but this condition is not necessarily considered unfair. On the other hand, as long as the compensation received remains proportional and meets the welfare aspect, the sense of justice is still felt in accordance with the principle of distributive justice which emphasizes the distribution of benefits fairly and properly between parties.